Active Learning of Contrast Sensitivity to Assess Visual Function in Macula-Off Retinal Detachment. (July 2021) - Thomas, Merina; Silverman, Rebecca F.; Vingopoulos, Filippos; Kasetty, Megan; Yu, Gina; Kim, Esther L.; Omari, Amro A.; Joltikov, Katherine A.; Choi, Eun Y.; Kim, Leo A.; Zacks, David N.; Miller, John B.
Purpose: This work characterizes the contrast sensitivity function (CSF) in patients with successful repair of macula-off rhegmatogenous retinal detachment (RD) using an adaptive computerized contrast testing device. Methods: CSF was prospectively measured in patients with macula-off RD following successful repair and age-matched controls at W.K. Kellogg Eye Center and Massachusetts Eye and Ear using Adaptive Sensory Technology's Manifold Contrast Vision Meter. Outcome measures included average area under the CSF curve, contrast-sensitivity thresholds (1-18 cycles per degree), and best-corrected visual acuity (BCVA) in RD eyes, fellow eyes, and controls. A subanalysis was performed in eyes with BCVA of 20/30 or better. Results: Twenty-three macula-off RD eyes following repair, fellow healthy eyes, and 45 age-matched control eyes underwent CSF testing. Mean BCVA of the 23 RD eyes was 0.250 logMAR, which was, significantly reduced compared with fellow eyes 0.032 ( P < .001) and controls 0.026 ( P < .001). There was a statistically significant reduction in average area under the CSF curve in RD eyes compared with fellow eyes ( P < .0001) and age-matched controls ( z score –0.90, P < .0001) and CSF reduction across all spatial frequencies. In the 15 RD eyes with BCVA of 20/30 or better, the mean CSF was significantly reduced vs fellow eyes ( P = .02) and controls ( P = .045). Conclusions: CSF in macula-off RD eyes following repair was significantly reduced compared with fellow eyes and age-matched controls. CSF may be a promising visual function end point with applications in clinical practice and future clinical trials.